In vitro comparative analysis of resistance to compression of laboratory resin composites and a ceramic system - Montenegro Alexandre; do Couto Cintia; Ventura Paulo; Gouvea Cresus; Machado Aldir (Wolters Kluwer Medknow Publications, 2010)
Background: Restorative materials must be capable not only of restoring the patient′s masticatory function, but also to rescue the self-esteem of those maculated by a disharmonious smile. Among the esthetic materials available on the market, the choice frequently lies between ceramic or indirect laboratory resin restorations. Aim: This study assessed the resistance to compression of two laboratory resins found on the market, namely Artglass ® and Targis ® , considering Omega 900 ® ceramic from Vita as control. Materials and Methods: With the aid of stainless steel matrices, with internal dimensions of 8.0 mm diameter at the base, 9.0 mm in the top portion and 4.0 mm height, 15 test specimens were made, being 5 of each material to be tested. The test specimens were kept in distilled water for 72 hours and submitted to an axial load by the action of a point with a rounded tip 2 mm in diameter, adapted to an EMIC 500 universal test machine. The compression speed was 0.5 mm/min, with a load cell capacity of 200 Kgf. Results: The means of the results were calculated in kilogram-force (Kgf). The results found were treated by analysis of variance (ANOVA) and the differences found among the groups were identified by the Tukey test (5%). Conclusion: It was observed that the material Omega 900 ® offered significantly greater resistance to compression than the other two materials, which did not present statistically significant difference between them.